2018
DOI: 10.1111/sms.13332
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde and oscillatory shear rate in young anabolic androgenic steroid users

Abstract: Disturbed shear rate (SR), characterized by increased retrograde and oscillatory SR in the brachial artery, is associated with inflammation, atherosclerosis, endothelial dysfunction, and sympathetic hyperactivity. Young subjects do not have disturbed SR; however, elderly subjects do, which seems to be associated with sympathetic hyperactivity. Anabolic androgenic steroids (AAS) abuse in young is associated with increased muscle sympathetic nerve activity (MSNA). We hypothesized that AAS users might have distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
8
0
6
Order By: Relevance
“…) and anabolic steroid use (de Souza et al . ). To examine the causality of OSS it can be experimentally induced in otherwise healthy upstream arteries by inflating a pneumatic cuff on the forearm to a moderate pressure (∼50–75 mmHg; Thijssen et al .…”
Section: Hypoxia and Endothelial Function In Lowlandersmentioning
confidence: 99%
“…) and anabolic steroid use (de Souza et al . ). To examine the causality of OSS it can be experimentally induced in otherwise healthy upstream arteries by inflating a pneumatic cuff on the forearm to a moderate pressure (∼50–75 mmHg; Thijssen et al .…”
Section: Hypoxia and Endothelial Function In Lowlandersmentioning
confidence: 99%
“…It is important that we evaluated a single, isolated AAS. Other studies have not reported standardization in blood sample collection times [70,120], in contrast to a previous study that reported collection between 10 and 12 a.m. [51].…”
Section: Discussionmentioning
confidence: 78%
“…AAS have been shown to increase low-density lipoprotein (LDL), decrease high-density lipoprotein (HDL) [36][37][38], reduce luteinizing hormone (LH) [39,40] and follicle-stimulating hormone (FSH) [37,41,42], decrease blood testosterone [43,44], and increase alanine transaminase (ALT) and aspartate transaminase (AST) [45], as well as other liver enzymes [38]. In those using AAS, basal blood shows increased hemoglobin [18,46], high hematocrit counts [47], and high in ammatory markers [48], including high white blood cell count [28], high neutrophil count [49], and high Creactive protein (CRP) [50,51]. These side-effects may result in costly treatment, and therefore a negative impact for public health [52].…”
Section: Introductionmentioning
confidence: 99%
“…However, misuse is commonly observed by athletes to promote strength increase, bodyweight and performance gain (1,3). Adverse events were associated with a variety of different cardiovascular diseases (4)(5)(6), liver disorders including peliosis hepatis, hepatocellular hyperplasia and carcinomas (7) and a spectrum of behavioral effects correlated with hyperandrogenism (8). Legitimate pharmaceutical grade AAS are illegally acquired in pharmacies.…”
Section: Introductionmentioning
confidence: 99%